Access to cardiac rehabilitation does not equate to attendance. (1st June 2014) - Clark, Robyn A; Coffee, Neil; Turner, Dorothy; Eckert, Kerena A; van Gaans, Deborah; Wilkinson, David; Stewart, Simon; Tonkin, Andrew M
Abstract: Background/Aims: Timely access to appropriate cardiac care is critical for optimizing positive outcomes after a cardiac event. Attendance at cardiac rehabilitation (CR) remains less than optimal (10%–30%). Our aim was to derive an objective, comparable, geographic measure reflecting access to cardiac services after a cardiac event in Australia. Methods: An expert panel defined a single patient care pathway and a hierarchy of the minimum health services for CR and secondary prevention. Using geographic information systems a numeric/alpha index was modelled to describe access before and after a cardiac event. The aftercare phase was modelled into five alphabetical categories: from category A (access to medical service, pharmacy, CR, pathology within 1 h) to category E (no services available within 1 h). Results: Approximately 96% or 19 million people lived within 1 h of the four basic services to support CR and secondary prevention, including 96% of older Australians and 75% of the indigenous population. Conversely, 14% (64, 000) indigenous people resided in population locations that had poor access to health services that support CR after a cardiac event. Conclusion: Results demonstrated that the majority of Australians had excellent 'geographic' access to services to support CR and secondary prevention. Therefore, it appears that it is not the distance to services that affects attendance. Our 'geographic' lens has identified that more research on socioeconomic, sociological or psychological aspects to attendance is needed.